2020
DOI: 10.1177/2043610619900519
|View full text |Cite
|
Sign up to set email alerts
|

Children’s education in ‘good’ nature: Perceptions of activities in nature spaces in mobile preschools

Abstract: In the Nordic countries, there is a culturally rooted understanding of nature as a ‘good’ place for children. The aim of the article is to deconstruct this understanding by exploring how different mobile preschools – buses that bring children to different places on a daily basis – relate to nature spaces and children’s learning and well-being in them. Based on critical theorization of place and the nature/culture divide, we argue that, while there exists an idealization of nature within the mobile preschool tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…The mooring places vary, although the direction is recurrently out of the city and into the countryside, and the destinations of choice are legitimized with reference to their nature and safety qualities. This collection of destinations is similar to other mobile preschools in Sweden (Gustafson and van der Burgt 2015), thereby following representational ideas of 'Nature's good' and 'Outdoor education' in ECEC (Halldén 2003;Harju et al 2020). We learn for instance that Mondays are destined for a natural playpark in a small forest just a few miles outside the city.…”
Section: The Designed Routementioning
confidence: 70%
See 2 more Smart Citations
“…The mooring places vary, although the direction is recurrently out of the city and into the countryside, and the destinations of choice are legitimized with reference to their nature and safety qualities. This collection of destinations is similar to other mobile preschools in Sweden (Gustafson and van der Burgt 2015), thereby following representational ideas of 'Nature's good' and 'Outdoor education' in ECEC (Halldén 2003;Harju et al 2020). We learn for instance that Mondays are destined for a natural playpark in a small forest just a few miles outside the city.…”
Section: The Designed Routementioning
confidence: 70%
“…The back and forth journeys are scheduled to thirty minutes each way, while time at the destinations varies depending on place and activities. Owing to the fact that destinations are foremost outdoors and daily activities are planned at 'nature' places, the mobile preschool presents itself as an educational option of place (Harju et al 2020) (rather than of mobility). The mobile preschool in the study is located in a middle-sized town in southern Sweden and comprises a permanent group of 16 children between the ages of three and five and three teachers, one of them assisting as a bus driver.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The conception shared by 19% of respondents that 'nature' is the outdoors is consistent with research by Hazula-Delay [12], who found when exploring conceptions of 'nature' that a common conception shared across their respondents was that 'nature' is 'out there'. Furthermore, the conception that the 'outdoors' is 'nature', along with interchangeable use of the two terms, is common across human-nature relationship literature (e.g., most recently, Harju et al [28], Sachs [29], White et al [30], Meredith et al [31]). This conception further explains the popularity of concepts such as biophilic design, the aim of which is bringing outdoor elements inside [32].…”
Section: Conceptions Of 'Nature'mentioning
confidence: 99%
“…Nature education, we argue, is one area in which such exclusionary processes are at work. Free outdoor play and explorations in "nature" have important roles as cultural practices that are taken for granted in early childhood pedagogies in the Scandinavian countries (Gulløv, 2012;Halldén, 2009;Harju, Balldin, Ekman Ladru & Gustafson., 2020). This involves strong expectations of 'sameness' (Gullestad, 2002) in children's relations to nature, as children are expected to "naturally" engage in outdoor play in all kinds of weather, and to enjoy it, just as parents are expected to support these practices, for instance by ensuring the right kind of outdoor clothing.…”
Section: "Nature-foreign" Children and Parentsaccess And Inclusion Inmentioning
confidence: 99%